Inhibition of nonmammalian glycosidases by azetidine iminosugars derived from stable 3,5-di-O-triflates of pentoses. - Lenagh-Snow, G; Araujo, N; Jenkinson, S; Rutherford, C; Nakagawa, S; Kato, A; Yu, C; Weymouth-Wilson, A; Fleet, G (2011)
Efficient ring closure of stable crystalline 3,5-di-O-triflates of pentofuranosides with amines to form azetidines allowed preliminary evaluation of four-ring iminosugars as glycosidase inhibitors; significant and specific inhibition of nonmammalian α-glucosidases is shown by L-xylo- and L-arabino-iminosugar azetidines.